104:oral Should the assessment of severity have a 'pandemic-premium'?. (28th April 2022) - Sandman, Lars
Abstract : The assessment of severity plays an essential role to conceptualize ideals about equity in several distributive theories and in mid-level operational principles in a number of healthcare jurisdictions, like Sweden, Norway and The Netherlands. Exactly how severity should be assessed is a matter of dispute, and it has been observed that several central issues concerning underlying rationales and operationalization are unresolved. One aspect, raised by the ongoing pandemic, but largely unanalyzed is how severity of a pandemic, like covid-19 should, be assessed. Within the ongoing Norwegian project SEVPRI, Horn et al made an interesting analysis of the severity of covid-19, raising several issues that do not seem to be fully covered by the Norwegian perspective on severity – and I would say generally so. One such issue is the indirect effect a pandemic has even for patients suffering mild disease, in terms of potential spread of disease to patients that will suffer individually severe conditions. In this talk I will explore whether the assessment of severity should take into account indirect effects in a pandemic and give a 'pandemic-premium' even to a mild condition, given the risk of spread and hence potentially severe consequences for other people. By comparing patient-populations where we in both cases effectively can avoid development of severe disease, in one case by treating people with mild disease and in one by treating people with severe disease, I will argue that we have a prima facie reason to either include a pandemic-premium to severity or add a further pandemic factor to consider. I will further explore how such a pandemic-premium should (and should not) be interpreted and explore some pros and cons of such a premium.